PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF PADA MATERI PENGARUH KALOR TERHADAP KEHIDUPAN DI SEKOLAH DASAR - Nurmiatun, Indah; Hakim, Zerri Rahman; Nurhasanah, Ana (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to determine the process of developing interactive PowerPoint learning media, feasibility and students’ response at elementary schools. The research method applied Research and Development (R&D) with the ADDIE model developed by Reiser and Mollenda. This research has five stages, namely: Analysis, Design, Develop, Implementation and Evaluation. This research and development involved a team of experts, including: media experts with a score of 91.67%, material experts with a score of 89.5% and language experts with a score of 66%. The average score obtained by all experts was 82.39% when interpreted as falling within the "Very Decent" criteria. Furthermore, supported by the calculation of the response questionnaire of students who took part in learning activities, the results were 92.36% reaching the "Very Good" category. So, it can be concluded that the product development of interactive PowerPoint-based learning media is "Very Appropriate" to be used as a media to assist learning activities. The results of student responses are "Very good" on the use of interactive PowerPoint products on theme 6 sub-theme 3 learning 1 for students at class V in SD Taman.